The Effect of Corporate Entrepreneurship and Organizational Culture on Business Performance: Evidence from Vietnam - Loc, Nguyen Duc; Minh, Ngo Ngoc (International Journal of Psychosocial Rehabilitation, 2020)
The paper examines the impact of organizational culture (OC), corporate entrepreneurship (CE) on business performance (BP) through supply chain performance (SCP) over the sample of 120 non-financial firms operating in Vietnam. The study finds that SCP fully mediates the relationship between work reinforcement & BP and time availability and BP. Whereas, SCP is found to have partial mediation in the relationship between CE & BP, OC & BP, management support & BP, organization boundaries & BP and reward reinforcement and BP. These findings are important in understanding and implementation of better OC which leads to CE and will enhance BP.